Analysis of pedestrian facility needs in tradisional indonesian market areas based on traffic characteristics and pedestrian volumes ( indonesian market area) - Diantori diantori; Ahmad Solikin; Ibrahim Nurhasan; Martinus Agus Sugiyanto; Mira Lestira Hariani (Riviera Publishing, 2024)
Crossing the road without crossing facilities is at great risk of traffic conflicts that can lead to congestion and accidents, so the availability of crossing facilities for pedestrians is an important indicator in improving pedestrian safety. This study aims to provide recommendations for the need for road crossing facilities that are in accordance with current conditions and the next 5 to 10 years in an effort to improve pedestrian safety. The method used is the LOS (Level Of Service) approach to determine traffic performance with calculations based on the Indonesian Road Capacity Guidelines (PKJI 2023), the PLOS (Pedestrian Level Of Service) approach to assess the performance of pedestrian facilities and to determine the appropriate type of crossing based on the guidelines of the Directorate General of Binamarga 2023 carried out by surveying traffic volume and crossing volume. The results showed that the study location has a LOS C value for current conditions and LOS E in the next 5 to 10 years. As for the PLOS value at the study site, it gets a score of F in the part that does not have pedestrian space, and a score of A in the part that has a pedestrian path. This study provides recommendations that there is a need for road crossing facilities in the form of